Historical Roots and Artistic Developments of Iraqi Theater: From Mosul to Baghdad - يسر منتصر خشلان (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
This research examines the development of Iraqi theatre from its early roots in Mosul during the late nineteenth century to its maturity in the capital, Baghdad, during the twentieth century. It emphasizes the importance of the religious and educational dimension in the emergence of this art form, before its transformation into a national cultural phenomenon. The research demonstrates how Mosul, with its diverse religious and cultural composition, formed an incubator environment for school theatre linked to Christian missionary schools, which used theatre as an educational and moral tool. Through this emergence, theatre began to take on a conservative local character, but it was soon influenced by European culture through translated and adapted texts, creating a fertile interaction between the local and the global. With the transfer of theatrical activity to Baghdad, theatre witnessed a qualitative shift supported by educational institutions such as the Institute of Fine Arts, and the establishment of official troupes, which paved the way for the emergence of a professional theatre movement linked to the concerns of Iraqi society. Baghdadi theatre played a prominent role in expressing social and political issues, adopting techniques such as “symbolic realism” as a means of circumventing censorship and integrating popular heritage with modern performance methods. The research confirms that The Mosul experience was a bridge between tradition and modernity, and ignoring it in Arab theater studies undermines the full understanding of the origins of Iraqi theater. The study adopted a historical analytical methodology based on primary and secondary sources. It concluded that Iraqi theater, despite its modest origins, was able to play a fundamental role in shaping national cultural identity. This research recommends documenting the Mosul period, incorporating the history of Iraqi theater into school curricula, supporting independent theater, and encouraging interaction with popular heritage as a contemporary creative resource.